Dystocia in Timorensis deer: a case report - Jeber, Z. K. H.; Che' Amat, Azlan; Abdullah, Faez Firdaus Jesse; Haron, Abdul Wahid (International Organization of Scientific Research, 2013)
In this case, a female Timorensis deer (Cervus timorensis) belong to Taman Pertanian Universiti (TPU), Universiti Putra Malaysia (UPM), was in labour for 5 hours. The limbs of the fawn were found hanging from the vulva at the general inspection. Request for veterinary assistance was initiated and the deer was isolated in dark room. Restraining was conducted physically without any tranquilizers or anaesthesia. On physical examination, foetus was found a live with posterior presentation and both hind limbs fully extended inside the birth canal. Manual traction was successfully performed to deliver the foetus. Following delivery the mother given proper care and the fawn was cleaned. The fawn was subsequently introduced to the mother and monitored to ensure suckling before being released to the farm.